2014
DOI: 10.1111/gcb.12631
|View full text |Cite
|
Sign up to set email alerts
|

Rising sea level, temperature, and precipitation impact plant and ecosystem responses to elevated CO2 on a Chesapeake Bay wetland: review of a 28‐year study

Abstract: An ongoing field study of the effects of elevated atmospheric CO2 on a brackish wetland on Chesapeake Bay, started in 1987, is unique as the longest continually running investigation of the effects of elevated CO2 on an ecosystem. Since the beginning of the study, atmospheric CO2 increased 18%, sea level rose 20 cm, and growing season temperature varied with approximately the same range as predicted for global warming in the 21st century. This review looks back at this study for clues about how the effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 59 publications
1
66
0
Order By: Relevance
“…In contrast, CO 2 fertilization work in brackish marshes of the North Atlantic supports increased growth and C gain by C‐3 species on long and short timescales (Drake, ; Langley et al, ; Pastore et al, ). These photosynthetic pathway‐specific differences in sensitivity to CO 2 concentrations may have implications for coastal wetland C cycling.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CO 2 fertilization work in brackish marshes of the North Atlantic supports increased growth and C gain by C‐3 species on long and short timescales (Drake, ; Langley et al, ; Pastore et al, ). These photosynthetic pathway‐specific differences in sensitivity to CO 2 concentrations may have implications for coastal wetland C cycling.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have found higher biomass in brackish marshes compared with both fresh (White and Simmons 1988) and saline (Valiela et al 1976;Linthurst and Reimold 1978a;Elsey-Quirk et al 2011) marshes. Different photosynthetic pathways may have contributed to observed variation in production (Cheng et al 2006;Cherry et al 2009;Drake 2014). Brackish marshes, dominated by the C 4 plant S. patens, had higher production rates than the fresh and intermediate marshes, which were dominated by C 3 plants.…”
Section: Discussionmentioning
confidence: 99%
“…Global freshwater and wetland ecosystems face multiple threats to their stability, including changes in land use, nutrient and toxicant pollution, and climate change 1, 2 . These disturbances could impair natural functioning (e.g.…”
Section: Introductionmentioning
confidence: 99%